In vitro antiplasmodial activity of phospholipases A2 and a phospholipase homologue isolated from the venom of the snake Bothrops asper (2012)
The antimicrobial and antiparasite activity of phospholipase A2 (PLA2) from snakes and bees has been extensively explored. We studied the antiplasmodial effect of the whole venom of the snake Bothrops asper and of two fractions purified by ion-exchange chromatography: one containing catalytically-active phospholipases A2 (PLA2) (fraction V) and another containing a PLA2 homologue devoid of enzymatic activity (fraction VI). The antiplasmodial effect was assessed on in vitro cultures of Plasmodium falciparum. The whole venom of B. asper, as well as its fractions V and VI, were active against the parasite at 0.13 ± 0.01 µg/mL, 1.42 ± 0.56 µg/mL and 22.89 ± 1.22 µg/mL, respectively. Differences in the cytotoxic activity on peripheral blood mononuclear cells between the whole venom and fractions V and VI were observed, fraction V showing higher toxicity than total venom and fraction VI. Regarding toxicity in mice, the whole venom showed the highest lethal effect in comparison to fractions V and VI. These results suggest that B. asper PLA2 and its homologue have antiplasmodial potential. © 2012 by the authors; licensee MDPI, Basel, Switzerland.